Sport Sponsorship as Cross-sectoral Collaboration and its Value for Young Customers - Mirońska, Dominika; Bergman, Antti (Journal of Corporate Responsibility and Leadership, 2020)
Purpose: The article discusses the benefits for companies and their customers as a result of collaboration with sport clubs on different advancement stages. Design/methodology/approach: The research takes a quantitative approach to study customers’ attitudes towards sponsorship in sports. The survey measures customers’ attitudes grouped in three categories: brand favourability, use of products, and perceived social input. It shows how these values change in different collaboration stages, defined by Austin’s (2000) Collaboration Continuum. Findings: The benefits were most effectively created on the philanthropic and integrative stages of collaboration with no statistically significant difference between the two. Further analysis of the results suggested the integrative stage to be the most favourable for companies to collaborate in, when taking into account the overall effect of collaboration. Research and practical implications: The research provides insight for both, business and non-profit managers in order to gain better understanding of the benefits of collaboration and what stage of collaboration results in highest perceived benefits. Originality/value: The research results may help both entities to manage their collaboration relationships. For non-profits this means understanding the value of their partnership and this way helping to create value propositions. For businesses this means the ability to engage in collaboration that brings best value for their customers and the company. Paper type: Research paper.